2019
DOI: 10.1177/0363546519886547
|View full text |Cite
|
Sign up to set email alerts
|

All-Suture Anchor Settling After Arthroscopic Repair of Small and Medium Rotator Cuff Tears

Abstract: Background: All-suture anchors are increasingly being used in rotator cuff repair. However, there are debates on the micromotion of all-suture anchors. Purpose: To perform rotator cuff repair on patients with rotator cuff tears and different shoulder bone mineral densities (BMDs) and investigate (1) where the anchor is located under the cortex, (2) if there is any anchor migration settling during follow-up, and (3) if structural outcome differs according to shoulder BMD. Study Design: Cohort study; Level of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…In their comparison across various suture anchors, Kim By contrast, in their retrospective review of 218 double-row repairs with hybrid fixation, Kim et al reported that 81 patients (37%) had grade 2 changes or more in medial-row soft anchors on MRI scans performed at a mean of 7 months postoperatively 6 . Their observed higher rate of cysts may be attributed to shorter follow-up as it has been demonstrated that the frequency and severity of fluid collections decrease with time 8 . In addition, the average angle of insertion in patients with and without cysts was 62°vs.…”
Section: Imagingmentioning
confidence: 96%
See 3 more Smart Citations
“…In their comparison across various suture anchors, Kim By contrast, in their retrospective review of 218 double-row repairs with hybrid fixation, Kim et al reported that 81 patients (37%) had grade 2 changes or more in medial-row soft anchors on MRI scans performed at a mean of 7 months postoperatively 6 . Their observed higher rate of cysts may be attributed to shorter follow-up as it has been demonstrated that the frequency and severity of fluid collections decrease with time 8 . In addition, the average angle of insertion in patients with and without cysts was 62°vs.…”
Section: Imagingmentioning
confidence: 96%
“…It should be noted, however, that follow-up in the studies where there was a relationship with perianchor fluid changes and retear was shorter than that in the studies that did not find an association. Because cysts decrease with time, longer follow-up may affect the association with cysts and retear 8 .…”
Section: Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…There are still doubts raised by reported cyst formations and potential secondary anchor failure. 18,19 Corresponding clinical outcomes studies are rare, 18,[20][21][22][23][24][25] and there is a lack of evidence for the clinical advantages of ASA compared to established implants.…”
mentioning
confidence: 99%